PEMANFAATAN BEKATUL SEBAGAI BAHAN DASAR MEDIA ALTERNATIF PERTUMBUHAN Aspergillus flavus - Oktaviani, Lu’lu Tsaniyah; Hamtini, Hamtini ,; Patricia, Venny; Armal, Hadits Lissentya (As-Syifaa Jurnal Farmasi, 2024)
Microbiology is the science that studies very small organisms, one of which is fungi. Fungi can grow and develop in a medium that contains sufficient nutrients. To identify the type of fungus, a growth medium is needed. Growth media is a substance consisting of a mixture of nutrients that support the growth of fungi, so it is necessary to make alternative media, one of which is using rice bran. The nutritional content of rice bran is 49.4 g carbohydrates, 24.7 g dietary fiber, 21.3 g fat, 16.5 g protein, 80 mg calcium, 2.1 grams phosphorus, 0.9 grams magnesium and 0.4 mg riboflavin vitamin. This research aims to determine the use of rice bran as a basic ingredient for alternative growth media for Aspergillus flavus. This type of research is an experiment by inoculating the Aspergillus flavus fungus using the Triple dot method. Observations were carried out for 7 days macroscopically by observing the diameter of the Aspergillus flavus fungus. The research results showed that there was an increase in colony diameter on rice bran media with concentrations of 8%, 10%, 12% and SDA media as a control of 29.3 mm, 33.0 mm, 33.8 mm and 34.9 mm. The effective concentration for the growth of the fungus Aspergillus flavus is a concentration of 12%. Based on the test results, it can be concluded that alternative media made from rice bran can be used as a growth medium for the fungus Aspergillus flavus.